Adjustment Models in 3D Geomatics and Computational Geophysics: With MATLAB Examples - Alsadik, Bashar (Computational geophysics, 2019)
This volume introduces a complete package of theoretical and practical subjects in adjustment computations related to geomatics and geophysical applications, particularly photogrammetry, surveying, remote sensing, GIS, cartography, geodesy, and computing. Presented in a simple way supported by illustrating figures and solved examples supported by MATLAB codes, the book provides clear methods for processing 3D data for accurate and reliable results.